A synchrotron X-ray diffraction study of in situ biaxial deformation. (15th May 2015) - Collins, D.M.; Mostafavi, M.; Todd, R.I.; Connolley, T.; Wilkinson, A.J.
Abstract: The biaxial deformation of a ferritic sheet steel has been examined using high energy in situ X-ray diffraction. A purpose built biaxial loading mechanism was constructed to enable deformation across a wide range of strain ratios. Three nominal deformation conditions were compared: (1) uniaxial loading, ∊ TD / ∊ RD = - ν, (2) biaxial deformation where ∊ TD / ∊ RD = 0.4, and (3) approximately balanced biaxial deformation, with ∊ TD / ∊ RD = 1.5 . This novel setup allowed the full Debye–Scherrer diffraction rings to be acquired during arbitrary selected strain-paths, permitting lattice strains and reflection intensities to be measured across an unrivalled grain orientation range for such deformation conditions. This experiment reveals that the accumulation of lattice strain during deformation, as a function of azimuthal angle, is highly sensitive to strain path. For the ∊ TD / ∊ RD = 1.5 strain path, whilst lattice strain accumulates most rapidly in the ∊ TD direction during early stages of plastic deformation, the lattice strain is shown to distribute almost perfectly isotropically for the observed orientations when plastic strain is high. This was found to be in contrast to strain paths where ∊ TD / ∊ RD ≪ 1.5, demonstrating that lattice strain magnitudes remain highest in the direction parallel to the tensile axis with the highest applied load. Furthermore, the technique provides the capability to observe the evolution of texture fibres via changes in reflection intensity during different applied strain ratios.